Evaluation of immunocomb in comparison with other serological tests in ovine brucellosis - Çetinkaya, B; Öngör, H (British Veterinary Assoc, 2000)
[Abstract Not Available]
Keywords: Linked-Immunosorbent-Assay; Melitensis Infection; Diagnosis; Sheep; Goats; Elisa; Strain; Pcr